Strategi Guru dalam Pembentukan Karakter Siswa Kelas VIII SMP Negeri 21 Ambon - Mustamu, Anike Klaras; Salong, Amjad; Latuserimala, Gerald (Universitas Pattimura, 2022)
This study aims to explore teachers’ strategies in shaping the character of eighth-grade students at SMP Negeri 21 Ambon. The background of this research stems from the phenomenon of declining moral values among adolescents and the central role of teachers in character education. This research uses a qualitative approach with a descriptive method. Data collection techniques involved in-depth interviews and documentation with teachers and students as the primary informants. Data were analyzed thematically to identify patterns in the applied strategies. The results show that three main strategies are employed by teachers: role modeling, spontaneous activities, and routine activities. Role modeling is carried out through the teachers’ everyday behavior, which serves as an example for students. Spontaneous activities include direct corrections and advice on students’ negative behaviors, while routine activities such as daily prayers, classroom cleaning duties, and flag ceremonies instill values like discipline, responsibility, and nationalism. These strategies have proven effective in shaping student character comprehensively. This study contributes to the development of a contextual, field-based model of character education. Its implications point to the need for teacher training and school policies that support the sustainability of character-building strategies